2020
DOI: 10.1021/acs.organomet.9b00794
|View full text |Cite
|
Sign up to set email alerts
|

SOMC@Periodic Mesoporous Silica Nanoparticles: Meerwein–Ponndorf–Verley Reduction Promoted by Immobilized Rare-Earth-Metal Alkoxides

Abstract: The Meerwein–Ponndorf–Verley (MPV) reduction is a reaction that offers a mild reduction of aldehydes and ketones to the corresponding alcohols. Although described as a catalytic reaction, its real-life applicability suffers from the necessity of using the standard catalyst [Al­(OiPr)3] in stoichiometric amounts or even in excess. Rare-earth-metal-based catalysts are capable of performing in these reactions in a truly catalytic fashion. The ceric alkoxide [Ce­(OiPr)4]3 has been synthesized via silylamine elimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…The cerium­(IV) alkoxides 5 (OR = OMe), 6 (OR = OEt), 7 (OR = OCH 2 t Bu), and 8 (OR = OCHMe 2 ) revealed characteristic NMR chemical shifts for the protons in the α-position of the alkoxy ligands (Ce–O–C– H ), as they appear heavily shifted downfield (Table ). Such a deshielding effect was also observed for the homoleptic cerium­(IV) alkoxides [Ce­(OCHMe 2 ) 4 ] 3 and [Ce­(OCH 2 t Bu) 4 ] 2 (thf), albeit to a minor extent. , The latter complexes show the relevant proton signals at 5.25 and 4.53 ppm, respectively, significantly shifted to lower field in comparison to 4.01 and 3.28 ppm in the free alcohol in CDCl 3 . ,, However, the 1 H NMR signals of the CH 2 moieties in neopentoxy derivatives Cp′ 3 Ce­(OCH 2 t Bu) ( 7a and 7b ) are detected at 5.87 and 6.09 ppm, respectively. This indicates a decrease in electron density at the respective protons close to the cerium­(IV) center, possibly caused by the +M effect of the alkoxy ligand.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…The cerium­(IV) alkoxides 5 (OR = OMe), 6 (OR = OEt), 7 (OR = OCH 2 t Bu), and 8 (OR = OCHMe 2 ) revealed characteristic NMR chemical shifts for the protons in the α-position of the alkoxy ligands (Ce–O–C– H ), as they appear heavily shifted downfield (Table ). Such a deshielding effect was also observed for the homoleptic cerium­(IV) alkoxides [Ce­(OCHMe 2 ) 4 ] 3 and [Ce­(OCH 2 t Bu) 4 ] 2 (thf), albeit to a minor extent. , The latter complexes show the relevant proton signals at 5.25 and 4.53 ppm, respectively, significantly shifted to lower field in comparison to 4.01 and 3.28 ppm in the free alcohol in CDCl 3 . ,, However, the 1 H NMR signals of the CH 2 moieties in neopentoxy derivatives Cp′ 3 Ce­(OCH 2 t Bu) ( 7a and 7b ) are detected at 5.87 and 6.09 ppm, respectively. This indicates a decrease in electron density at the respective protons close to the cerium­(IV) center, possibly caused by the +M effect of the alkoxy ligand.…”
Section: Resultsmentioning
confidence: 66%
“…Such a deshielding effect was also observed for the homoleptic cerium(IV) alkoxides [Ce(OCHMe 2 ) 4 ] 3 and [Ce(OCH 2 tBu) 4 ] 2 (thf), albeit to a minor extent. 22,39 The latter complexes show the relevant proton signals at 5.25 and 4.53 ppm, respectively, significantly shifted to lower field in comparison to 4.01 and 3.28 ppm in Scheme 1. Oxidation of Cp R 3 Ce(thf) (1), 14,32 to Form Cerium(IV) Halogenides 2-4 The ceric tris(cyclopentadienyl) complexes under study could be obtained as needlelike microcrystals via crystallization from n-hexane.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…On the other hand, to overcome the drawbacks of the homogeneous catalysts in catalyst contamination in reaction outcomes and poor recyclability, increasing interest has been directed toward developing supported catalysts in surface organometallic chemistry (SOMC). Such catalysts not only show the high activity of homogeneous catalysts but also display the ease of separation and recyclability of heterogeneous catalysts, allowing for better control of the whole synthetic process. Consequently, the immobilized heterogeneous rare-earth metal complexes have received much interest in SOMC and have demonstrated interesting performance in organic synthesis and polymerization. Very recently, we developed the well-defined silica-grafted rare-earth metal benzyl materials Ln­(CH 2 C 6 H 4 NMe 2 - o ) 3 @SBA-15 (Scheme ) and found that they exhibited extremely high selectivity and good recyclable property in the transformation of primary arylsilanes into secondary arylsilanes through redistribution. , This interesting finding prompted us to explore their catalytic potential in other organic transformations. Inspired by the elegant work reported by the Marks group and the Chen group using rare-earth metal complexes Ln­[N­(SiMe 3 ) 2 ] 3 as catalysts in amide reduction, , it was envisaged that Ln­(CH 2 C 6 H 4 NMe 2 - o ) 3 @SBA-15 (Ln–C σ-bonded species) possesses promising catalytic performance in amide reduction owing to its bond disruption enthalpy comparable to the amide analogues (Ln–N σ-bonded complexes) .…”
Section: Introductionmentioning
confidence: 99%